Influence of recycled electronic waste fiber on the mechanical and durability characteristics of eco-friendly self-consolidating mortar incorporating recycled glass aggregate - Saingam, Panumas; Chatveera, Burachat; Roopchalaem, Jutatip; Hussain, Qudeer; Ejaz, Ali; Khaliq, Wasim; Makul, Natt; Chaimahawan, Preeda; Sua-iam, Gritsada (My University, 2025)
In the paper, the sustainable production of eco-friendly self-consolidating mortar (SCM) is explored with waste glass as a partial and complete substitution for fine aggregate owing to crucial environmental concerns. For that, the waste glass was replaced at 0 %, 25 %, 50 %, 75 %, and 100 %, while electronic waste fibers were added at 5, 10, and 15 % levels. Results showed that mini slump flow values varied between 233 mm and 263 mm, which confirmed the self-consolidating properties of the material even at 100 % replacement of fine aggregates and an addition of 15 % fiber. The increase in waste glass replacement reduced compressive strength; notably, a 30 % decrease was identified at the maximum substitution level of 100 %. Meanwhile, the mixtures incorporating 5 % fibers demonstrated the highest compressive strength at all maturation periods and replacement levels, even more markedly than the control mixture. The water absorption also increased significantly with increasing waste glass levels, up to 28.87 % at 100 % replacement, indicating increased porosity. Thermal conductivity decreased substantially, ranging from 1.97 W/mK for the control to 1.39 W/mK for 100 % replacement, which could be considered an improvement in insulation properties. These results show the possibility of using waste glass and electronic waste fibers to develop green SCM with enhanced thermal insulation and optimized mechanical properties.
Keywords: Fine aggregate; Mechanical properties; Recycled electronic waste fiber; Self-consolidating mortar; Waste glass